The Effectiveness of Backward Chaining Methods to Improve Skills in Children with Intellectual Disability - Arip Apriyadi; Mohammad Efendi; Sulthoni Sulthoni (Department of Special Education, 2017)
A child with intellectual disability has problems in adaptive behavior such as eating skill. The research objective was to describe: 1) the ability of the child with intellectual disability before being given intervention using backward chaining method, 2) the ability of the child with intellectual disability after being given intervention using backward chaining method, and 3) the effectiveness of backward chaining method to increase the eating skills for child with intellectual disability. The method of this study was an experimental method by using the Single Subject Research (SSR) with the A-B-A design model. The results showed that the percentage of overlap between the baseline condition-1 and the intervention condition was 0%. The calculation declared that there was increase eating skill for child with intellectual disability with backward chaining.Anak disabilitas intelektual memiliki masalah dalam perilaku adaptif seperti pada keterampilan makan. Tujuan penelitian ini untuk mendeskripsikan: 1) kemampuan anak disabilitas intelektual sebelum diberikan intervensi menggunakan backward chaining, 2) kemampuan anak disabilitas intelektual setelah diberikan intervensi menggunakan backward chaining, dan 3) keefektifan backward chaining untuk meningkatkan keterampilan makan. Metode penelitian yang digunakan dalam penelitian ini adalah metode eksperimen dengan menggunakan Single Subject Reseach (SSR) dengan desain A-B-A. Hasil penelitian menunjukan perolehan presentase overlap antara kondisi baseline-1 ke kondisi intervensi sebesar 0%. Perhitungan tersebut menyatakan adanya pengaruh keefektifan backward chaining sebagai intervensi terhadap peningkatan keterampilan makan sebagai target behavior.DOI: http://dx.doi.org/10.17977/um029v4i12017p037